Shaping The Future of Engineering Education Through Artificial Intelligence and Innovation - Kumar, Anuj; Pujari, Purvi; Eldebeky, Sayed M.; Pillai, Rajani H. (Journal of Engineering Education Transformations, 2025)
No Abstract.